Is the Water Supply a Key Factor in Stingless Bees' Intoxication?. Issue 6 (12th November 2020) - Rosa-Fontana, Annelise de Souza; Dorigo, Adna Suelen; Soares-Lima, Hellen Maria; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar
Abstract: Water is an important resource for stingless bees, serving for both honey dilution and the composition of larval food inside nests, yet can be an important route of exposure to pesticides. Assuming bees can forage naturally on pesticide-contaminated or noncontaminated areas, we investigated whether water supply influences the choice between neonicotinoid-dosed or nondosed feeders and on mortality of the stingless bee, Melipona scutellaris (Latreille, Hymenoptera, Apidae). At the field concentration, there was no significant mortality; however, the bees were not able to distinguish the feeders. In the cages containing high-concentration feeders, with water supply, the bees preferred nondosed food, and with no water, the mortality increased. Considering that in the field it is common to find extrapolated concentrations, our work suggested that water may allow avoidance of high dosed food and minimize mortality.